ANALISIS SPEKTROFOTOMETRI EKSTRAK BUNGA TELANG BERDASARKAN VARIASI WAKTU MASERASI SEBAGAI KANDIDAT SENSITIZER PADA DYE SENSITIZED SOLAR CELL (DSSC) - Fadia Mutiara Putri; Sherly Kasuma Warda Ningsih (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Increasing population growth causes an increase in energy demand, which causes global warming and climate change. Therefore, a renewable energy source is needed, namely solar energy. DSSC offers the potential for lower production costs compared to conventional solar cells. However, currently the commonly used sensitizer is ruthenium-based which is expensive and harmful to the environment. Therefore, a natural sensitizer is sought, namely from butterfly pea flowers which contain anthocyanin pigments that can absorb light and convert it into electrons. The purpose of this study was to determine the functional groups of butterfly pea flowers and determine the effect of maceration time on the maximum wavelength of butterfly pea flower extract as a sensitizer candidate in DSSC. The method used was maceration of butterfly pea flower powder using 70% ethanol solvent with variations in maceration time, namely 24 hours, 48 hours and 72 hours. Spectrophotometric analysis was carried out using FTIR to determine the functional groups contained in butterfly pea flowers and UV-Vis to determine the maximum wavelength in butterfly pea flower extract. The result is that there is a strong absorption band at a wave number of 3279.96 cm-1 indicating the presence of O-H group stretching which indicates that the butterfly pea flower is rich in anthocyanins. The maximum wavelength of the butterfly pea flower is that there are 2 peaks at 576 nm and 621 nm. Variations in maceration time do not affect the maximum wavelength of the butterfly pea flower but affect the absorbance, the lowest absorbance is 24 hours of maceration time followed by 48 hours of maceration time and the highest is 72 hours of maceration time. The conclusion is that the main compound contained in the butterfly pea flower is anthocyanin and 72 hours of maceration time shows the highest absorbance so it can be used as the most optimal sensitizer candidate.